An Overview of Methods and Tools for Transfection of Eukaryotic Cells in vitro - Fus-Kujawa, Agnieszka; Prus, Pawel; Bajdak-Rusinek, Karolina; Teper, Paulina; Gawron, Katarzyna; Kowalczuk, Agnieszka; Sieron, Aleksander L. (Frontiers in Bioengineering and Biotechnology, 2021)
Transfection is a powerful analytical tool enabling studies of gene products and functions in eukaryotic cells. Successful delivery of genetic material into cells depends on DNA quantity and quality, incubation time and ratio of transfection reagent to DNA, the origin, type and the passage of transfected cells, and the presence or absence of serum in the cell culture. So far a number of transfection methods that use viruses, non-viral particles or physical factors as the nucleic acids carriers have been developed. Among non-viral carriers, the cationic polymers are proposed as the most attractive ones due to the possibility of their chemical structure modification, low toxicity and immunogenicity. In this review the delivery systems as well as physical, biological and chemical methods used for eukaryotic cells transfection are described and discussed.